Penerapan Intervensi "Pelangi Emosi" Berbasis Seni dalam Meningkatkan Kemampuan Regulasi Emosi Anak Berkebutuhan Khusus di Panti Asuhan X - Arthauli Claudya Agnescia Ambarita; Dina Oktavia; Shienny Felynda; Pamela Heng Lukas; Hanna Christina Uranus (YASIN, 2026)
Emotion regulation is an individual’s ability to control behaviors that are inconsistent with the emotions experienced and to manage oneself so as not to depend on either negative or positive moods. Based on observations and interviews conducted during the implementation of the Merdeka Belajar Kampus Merdeka Program at Orphanage X, children with special needs exhibited various emotional challenges, such as tantrums, impulsive behavior, and difficulties expressing emotions. This study aims to develop and evaluate an activity-based intervention module to improve the emotion regulation abilities of children with special needs at Orphanage X. The study employed a research and development method comprising the stages of needs analysis, design, trial, and evaluation. The intervention module integrates collective painting activities, educational games, video presentations, and emotion activity sheets designed for easy implementation by caregivers. The results of the module implementation showed improvements in the children’s ability to recognize emotions, a reduction in negative emotional responses, and increased social participation. The novelty of this study lies in the integration of collective art activities as a medium for emotion regulation, systematically organized and adapted to the characteristics of the children at Orphanage X. This study provides a practical contribution in the form of an original and applicable intervention module to support caregivers in facilitating the emotional and social development of children with special needs.